Impact of languages to speech privacy and intelligibility of closed spaces - Ma, Y.; Caswell, D.J.; Dai, L.; Goodchild, J.T. (Canadian Acoustics, 2005)
The present study investigates the speech privacy and intelligibility of closed spaces in multicultural environments. Most assessments for speech privacy and speech intelligibility among the current research rely on the subjective measurements utilized with the test materials of English and other Western languages. Effects of different languages and accents in speech privacy and speech intelligibility are usually overseen. Subjective measurements are conducted in this study for closed spaces by using English and a tonal language. The differences in speech privacy between the two languages are evident and significant. It is also found in this study that the existing single word tests used in research and industrial practice for subjectively evaluating speech privacy need modification when closed spaces are considered. The subjective measurement results of this study are compared with the objective measurement index AI.